Video Streaming over D2D Networks - Ahmed, Ibtihal Mohamed Taha (2019)
A Master of Science thesis in Electrical Engineering by Ibtihal Mohamed Taha Ahmed entitled, “Video Streaming over D2D Networks”, submitted in April 2019. Thesis advisor is Dr. Mahmoud H. Ismail Ibrahim and thesis co-advisor is Dr. Mohamed S. Hassan. Soft and hard copy available.